Formulation and Stability Evaluation of Antioxidant Sunscreen Gel Containing Green Tea Leaf (Camellia sinensis) Extract Using the DPPH Method - Jhon Patar Sinurat; Zahara Fitria; Reh Malem Br Karo; Shofian Syarifuddin (Jurnal FARMASIMED (JFM), 2026)
Sunscreen formulations are designed to protect the skin from exposure to ultraviolet (UV) radiation; however, excessive use of synthetic ingredients may lead to adverse effects on the skin. The utilization of natural ingredients as alternatives has gained increasing attention, one of which is green tea leaves (Camellia sinensis), known for their rich antioxidant content. This study aimed to formulate and evaluate the stability and antioxidant activity of a sunscreen gel based on green tea leaf extract. This research was a laboratory-based experimental study employing a quantitative approach with a post-test only control group design. The gel formulations were prepared in four variations of extract concentration, namely 0% (F0), 5% (F1), 10% (F2), and 15% (F3). The preparations were then evaluated for physical characteristics, irritation potential, and antioxidant activity using the DPPH method. The results showed that 392 g of extract was obtained from 3.8 kg of dried simplicia, yielding a 10.32% extraction yield. Phytochemical screening indicated the presence of flavonoids, tannins, saponins, and alkaloids. All formulations exhibited a semi-solid form, good homogeneity, and stable pH values ranging from 6.0 to 6.3, which are compatible with skin pH. Furthermore, no irritation reactions were observed among the 12 volunteers. Antioxidant activity increased with higher extract concentrations, with IC₅₀ values of 28.86 ppm (F0), 22.11 ppm (F1), 21.25 ppm (F2), and 20.72 ppm (F3). In addition, the percentage of inhibition for F0–F3 also showed an increasing trend, namely 8.24–17.50%, 15.79–26.28%, 13.30–24.89%, and 14.82–26.25%, respectively. In conclusion, green tea leaf extract demonstrates strong potential as an active ingredient in sunscreen gel formulations that are safe, stable, and possess significant antioxidant activity.